ANALISIS KEMAMPUAN SISWA PADA MATERI SEGIEMPAT DAN SEGITIGA DITINJAU DARI KONEKSI MATEMATIKA (STUDI KASUS PADA SISWA KELAS VII SMP UNISMUH MAKASSAR) - Mufidah Mufidah; Suradi Tahmir; Ilhamuddin ilhamuddin (SIGMA: JURNAL PENDIDIKAN MATEMATIKA, 2022)
The focus of this research is "how is the ability of the seventh grade students of SMP Unismuh Makassar to connect mathematics on the material of quadrilaterals and triangles." The approach used is a qualitative descriptive approach. The research subjects were seventh grade students of SMP Unismuh Makassar which consisted of 1 student who had high mathematical connection ability, 1 student who had moderate mathematical connection ability and 1 student who had low mathematical connection ability. The instrument used is a test of the ability of mathematical connections in the material of quadrilaterals and triangles. The results obtained from this study are students who have high mathematical connection skills have no difficulty in solving mathematical problems with quadrilateral and triangle material. Students who have moderate mathematical connection abilities tend to have difficulty in indicators of applying and connecting concepts between mathematical material. And students who have low mathematical connection abilities have not met the indicators of applying mathematical concepts in solving mathematical problems related to everyday life.